Rickets in a High Social Class of Renaissance Italy: The Medici Children. (28th May 2013) - Giuffra, V.; Vitiello, A.; Caramella, D.; Fornaciari, A.; Giustini, D.; Fornaciari, G.
Abstract Exploration of the Medici Chapels in the Basilica of San Lorenzo in Florence revealed the burials of nine juvenile members of the Medici family (16th–17th centuries). The estimated children's skeletal ages ranged from newborns to 5‐year‐olds, showing a series of bone abnormalities, in particular diffuse periosteal new bone and bowing of long bones. The comparable pathological lesions, including porosity evident on the skull, orbital roofs, costocondral ribs and growth plates between metaphyses and epiphyses, enlargement of metaphyses and sternal rib ends, and long bone bending, are interpreted as the skeletal manifestation of rickets. The diagnosis of a metabolic disease linked to vitamin D deficiency would appear to be unexpected for children brought up at the court of a Renaissance elite class family like the Medici of Florence. Analysis of the historical and social background is particularly helpful to understand the causes of the onset of the disease in this aristocratic group. Documentary sources, supported by 13C and 15N bone collagen analysis, attest that weaning of these children took place when they were around 2 years old. With a prolonged breast‐feeding and a delay in introducing solid food in the diet, vitamin D deficiency is expected to rise considerably, in particular if the other main risk factor, namely inadequate sunlight exposition, is associated with this human milk‐based diet. Copyright © 2013 John Wiley & Sons, Ltd.